BUSINESS ADMINISTRATION MODEL INNOVATION AND “TAM” THEORY DEVELOPMENT IN IMPROVING STUDENT ONLINE BUSINESS PERFORMANCE - Amelia Setyawati; Rahma, Adelia; Hidayat, Rachmad; Melany; Sudarjo; Sutomo; Ibadil Maula, Farij (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: This study examines the phenomenon of online business readiness among students, which is increasingly important in today's digital age. With the rapid development of technology and the internet, it is important for students to have adequate skills in running an online business. Purpose: The purpose of this study is to explore the factors that influence students' readiness to engage in online entrepreneurship, as well as to provide insights into how education can support the development of these skills. Novelty: This study offers a new framework that combines TAM Theory and business learning innovation as determinants of student online business performance. In addition, the mediating variable Attitude Toward Using provides a new perspective in understanding how attitudes toward technology can strengthen the relationship between these factors and online business readiness. Research Methods: This study uses explanatory research with a quantitative approach. The research population consists of students from public and private universities in East Java. Results: The results show that students are well prepared to engage in online business, with high scores in technological capabilities and network support. However, challenges remain, particularly in terms of business experience and access to capital. Research Contributions: This research contributes to a better understanding of students' readiness for online business and suggests steps that educational institutions can take to improve entrepreneurial skills among students